Islamic Education Planning Strategy at SMP Al-Wasliyah Berastagi - Yusuf Hadijaya; Yuni Syafriani; Suci Ramadhani; Fella Annisa Harahap (Universitas Muhammadiyah Enrekang, 2022)
Educational planning in planning management in the field of Islamic education, the ultimate goal is to improve the quality, output competitiveness (graduates) with indicators of both intellectual competence and skills as well as high social competence of students/graduates. In achieving these results, the implementation of educational planning in quality management in Islamic education organizations needs to be done in real terms, not half measures. By utilizing all the quality entities that exist within the organization, our education will not run as it is today. Implementation of education quality management planning in organizations, especially in Islamic education institutions is not easy. There are obstacles in the work culture, the performance of teachers and employees greatly affects. It cannot be denied that the work culture, performance and discipline of civil servants in our country are very low. This greatly affects the effectiveness of the implementation of quality education.